Revisiting Women Empowerment:A Review Of Policies On Landuse And Food Security In Zimbabwe. - Dzvimbo, Munyaradzi Admire; Monga, Monica; Mashizha, Tinashe M. (Advances in Social Sciences Research Journal, 2018)
The Land question in Zimbabwe and most countries of the Global South has always been marred by the injustices perpetrated by the colonial governments in the equitable distribution of land. Women have been severely disadvantaged yet they are the ones who contribute so much in agricultural production and food security. Thus, land tenure, ownership, food security and access are interlinked, directly and indirectly. This paper seeks to explore while revisiting policies that have addressed land-use, tenure security and ownership in relation with women in Zimbabwe. Women have always been a domineering force in agriculture in which they contribute immensely though their contributions has not been fairly chronicled and publicised. Thus land is a key resource to empowering women in the socio- economic growth trajectory and poverty alleviation. Successful realisation entails a functioning transparent land administration system. Hence, access to arable and productive land is vital to most women who live in the communal areas and depend wholly on farming for their livelihoods. It is in this realm that, land plays a significant part and as a socio-economic catalyst, policies inclined should clearly state the position of women as far as ownership is concerned. Various statutory and legal statutes should address rights of women so that they will be able to continue contributing to food security. In light of these objections, this paper further examines and explores current and also already researched literature on empowering women in the lenses of land-use, right, access and their contributions to food security.